Students’ Perceptions of the Literature Circles Method in English Learning at SMKN 1 Toraja Utara - Palulun, Demma; Sallata, Yizrel Nani; Tulaktondok, Linerda (Jurnal Studi Guru dan Pembelajaran, 2023)
This study investigates students’ perceptions of the integration of Literature Circles as a strategy in English language learning among eleventh-grade students in the TKJ (Computer and Network Engineering) program at SMKN 1 Toraja Utara, Indonesia. Literature Circles are a student-centered approach where learners engage in small group discussions based on selected literary texts. This method aims to promote reading comprehension, encourage communication, foster collaborative learning, and develop critical thinking in a supportive environment. A total of 54 students participated in the study by completing a structured questionnaire consisting of 28 statements 14 positive and 14 negative related to their experiences with Literature Circles. The questionnaire was administered using a Likert scale format to quantify levels of agreement, allowing for a detailed analysis of student perceptions. The results show a predominance of positive student responses. More than 80% of the participants “strongly agreed” that Literature Circles positively impacted learning and personality (88.88%), improved communication with teachers (88.14%), encouraged meaningful peer interaction (86.66%), and enhanced reading comprehension (86.29%). Students also acknowledged the method’s ability to build responsibility, motivation, and critical thinking. However, the study also uncovered key challenges, including perceptions of unclear teacher roles (78.14%), inconsistent evaluation practices (71.48%), and the marginalization of less confident or less proficient students (70.37%). Other concerns involved unstructured group discussions and difficulties in choosing appropriate texts, highlighting the importance of scaffolding and teacher facilitation. These findings suggest that while Literature Circles are generally effective in promoting engagement and language development, their implementation requires thoughtful planning, especially in vocational education settings where learner diversity and varying literacy levels are common. A balance between student autonomy and structured guidance is essential to optimize the learning outcomes of all participants.